The Effectiveness of Community-Based Programs on Older Adult\'s Subjective Well-Being - Malihe Shiani; Hannan Zare (University of Social Welfare & Rehabilitation Sciences, 2013)
Objectives: Intensified increasingly in older adult population bring about to focus on these people problems in many developed countries. Among methods, community-based programs are the new way to counter older adult's problems. Although performance of these programs being in the earliest stage of development, this study has examined the effectiveness of community-based programs on older adults’ subjective well-being in Kahrizak. Methods & Materials: 100 elders above 60 years in Kahrizak were selected completely random sample. 50 elders had participated in the program (experimental group), 50 elders hadn’t participated (sub group).the method was interference. The data was gathered by questionnaire technique and interview and was analyzed by spss. Results: The average of experimental group subjective well-being was 2.55 and the sub group was -1.34. Elder members of Kahrizak who have used services in community-based programs and have given significant services have had more subjective well-being measure than sub group. Conclusion: Although this program isn’t performance for a long time, they have significant effects on older adults’ subjective well-being responsive to the models and theories. Elders who have participated in the programs remained more independently in the community. Happiness, quality of life, life satisfaction, and domain satisfaction have been increased by using the community-based programs.